Breast Cancer Awareness among Bahawalpur Women through Art and Design - Maria Ansari; Farjad Faiz; Shumaila Qureshi (Indus Journal of Social Sciences, 2025)
Breast Cancer is a jeopardy disease now a day. It is not a disease of females; males are also suffering from this disease one out of every nine women and one out of twenty men are at risk of breast cancer. In Pakistan, it increases day by day due to lack of awareness. This study was led to assess the role of awareness among the young girls and boys. The main purpose of the study was aware the male and female about the disease that they can save their selves from the risky factors. The universe of the study of Bahawalpur District and population was the person who had completed their probation period. This was a qualitative study using probability method for selecting respondents and interview schedule was used for data collection and data was analyzed through SPSS. Result indicates that awareness can save the person from the disease. Self-examine method and awareness sections are not accessible commonly. Furthermore, there are not proper examine station available in every health care centers. More studies are advised in this disease and there is need to establish more centers to education the young male and females about the method of self-examine which could save them from risk factors.